Assembly of Dihydropyridazines via [4+2] Cycloaddition of In Situ Generated Azoalkenes. Issue 2 (16th January 2023) - Yuan, Cheng; Wang, Jiatong; Wang, Gangqiang; Sun, Shaofa; Wang, Jian
Abstract: The unprecedented example for the synthesis of multi‐substituted pyridazines via [4+2] cycloaddition of azoalkenes generated in situ is described. This protocol features broad substrate scope and allows rapid assembly of pyridazines. Notably, this process provides an alternative method for in situ generation of azoalkenes. Abstract : The synthesis of multi‐substituted pyridazines via [4+2] cycloaddition of azoalkenes generated in situ is described. This protocol features broad substrate scope and allows rapid assembly of pyridazines. The synthesis route provides an alternative method for in situ generation of azoalkenes from hydrazones and sulfur ylides.